Diferencias en las dimensiones mandibulares en pacientes con terceros molares impactados y no impactados (2023)
The lower third molars are teeth with a high tendency for impaction, which can lead to problems during orthodontic diagnosis and treatment. Little is known about the role of the third molars in the dental arch dimensions as well as skeletally and how they interact.to determine changes between erupted and impacted third molars. Therefore, the aim of this study was to compare the changes in mandibular dimensions when impacted and non-impacted third molars